Simple preparation of new N-aryl-N-(3-indolmethyl) acetamides and their spectroscopic analysis - José A. Henao; Josué S. Bello; Vladimir V. Kouznetsov; Diego F. Amado; Reinaldo Atencio (Universitas Scientiarum)
To prepare new indolic molecules and characterize them by spectroscopic methods. Materials and methods: All reagentswere purchased from Aldrich, commercial grade. The purity of the products and the composition of the reaction mixtures were monitoredby thin layer chromatography over Silufol UV254 0.25 mm-thick chromatoplates. Product isolation and purification were performed bycolumn chromatography (SiO2), using ethyl acetate-petroleum ether mixtures as eluents. Results. The synthesis of new N-aryl-N-(3-indolmethyl) acetamides based on first step iminization reaction of indol-3-carbaldehyde is accomplished. The structures of the C-3substituted indoles were confirmed by 1H-NMR and 13C-NMR studies supported by inverse-detected 2D NMR experiments and alsothrough monocrystal X-ray diffraction. Conclusions. An efficient, economic, and fast synthetic route was designed to the construction ofthe N-aryl-N-(3-indolmethyl) acetamides, structural analogues of some alkaloids.